PENGGUNAAN "PARTIAL ADJUSTMENT MODEL" SEBAGAI ALTERNATIF ALAT ANALISIS DAYA SAING KOMODITAS PERTANIAN DALAM PERDAGANGAN INTERNASIONAL - RACHMAT HENDAYANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
There are some tools for competitive advances analysis in international trade commoditythat one is “Partial Adjustment Model” (PAM). The PAM methods can be estimate through linierregression or logarithm, while competitive advantage parameter shown by elasticity coefficient. ThePAM methods applying in pepper trade using Pepper Statistical Years Book for more years fromInternational Pepper Community (IPC), shows that Indonesian pepper export share is equal withMalaysia. There is show increase. Elasticity coefficient for market share to pepper price in the worldis relatively small than Malaysia both in short term as well as long term i.e. about 0.07 and 0.013respectively. This condition show that world pepper price exchange for pepper Indonesian export isnot elastic.